1992
DOI: 10.1007/bf00175475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3-morpholinosydnonimine (SIN-1) and NG-nitro-l-arginine (NNA) on isolated perfused anaphylactic guinea-pig hearts

Abstract: The modulating effects of exogenous and endogenous nitric oxide (NO) on the cardiac anaphylactic reaction and eicosanoid release were investigated in isolated perfused sensitized guinea-pig hearts using 3-morpholinosydnonimine (SIN-1), the active metabolite of molsidomine, as NO-donor and NG-nitro-L-arginine (NNA) as an inhibitor of NO biosynthesis. Infusion of SIN-1 (final concentrations in the perfusates 0.3 or 1.0 mmol/l) elevated coronary flow under basal conditions as well as during cardiac anaphylaxis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Indeed, inhibition of NO synthesis aggravates anaphylactic constriction of regional vasculature, such as coronary artery (27) and pulmonary circulation (23). We herein showed that NO inhibition pronounced hepatic anaphylactic venoconstriction.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Indeed, inhibition of NO synthesis aggravates anaphylactic constriction of regional vasculature, such as coronary artery (27) and pulmonary circulation (23). We herein showed that NO inhibition pronounced hepatic anaphylactic venoconstriction.…”
Section: Discussionmentioning
confidence: 48%
“…With respect to the effects of NO on anaphylaxis, NO contributes to acute hypotension of anaphylaxis (20). NO also modulates anaphylaxisinduced changes in regional hemodynamics of coronary circulation (27) and pulmonary circulation (23) by serving as an endogenously released vasodilator. However, it has not been known whether NO modulates the change in hepatic hemodynamics during anaphylaxis.…”
mentioning
confidence: 99%
“…The produced nitric oxide activates cGMP, which subsequently causes vasodilatation in smooth muscle cells [15] and possibly decreases contractility in myocytes [14]. In vitro studies have shown that NO functionally antagonizes the effects of the vasoconstrictors released during anaphylaxis [16] as well as that NO production might reduce some pathophysiological changes associated with anaphylaxis, except for vasodilatation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to SNP, SIN-1 appeared to be less potent and effective in raising cutaneous blood flow, which is in line with its relatively low relaxant activity in other vascular beds (Thelen et al, 1992). Further, albeit inconclusive, evidence for NO being the active entity came from the ability of methylene blue to attenuate the vasodilator response to SNP.…”
mentioning
confidence: 92%